Consumption and redistributive politics: The effect of credit and China. (June 2013) - Kus, Basak
This article attempts to bring consumption into the study of redistributive politics. Analyzing data from 20 OECD countries over the period 1995–2007, I investigate whether factors that allowed lower and middle-income households to sustain their consumption had any impact on governments' redistributive efforts. The article focuses on two factors in particular: access to credit and access to cheap imports (notably, imports from China). I argue that by enhancing consumption these mechanisms moderated the effects of income inequality and suppressed public discontent with increasing income inequality, thereby lessening the political urgency of redistribution.